Online self-management fall prevention intervention for people with multiple sclerosis: a feasibility study protocol of a parallel group randomised trial - Maria Flink; Elizabeth Peterson; Charlotte Ytterberg; Marie Elf; Kristina Gottberg; Marie Kierkegaard; Susanna Tuvemo Johnson; Sverker Johansson (BMJ Open)
Introduction Falls among people with multiple sclerosis (PwMS) are common and associated with injuries, fear of falling and low health-related quality of life. Considerations of behavioural, environmental, psychological and physical influences (including ambulation status) are needed to meet fall prevention needs for PwMS. Thus, using a codesign process involving key stakeholders a novel online self-management fall prevention intervention was created specifically for ambulatory and non-ambulatory PwMS. The feasibility, acceptability, fidelity and outcome of this complex intervention will be explored. Findings will inform a future full-scale randomised controlled trial.Methods and analysis A mixed-method design will be used. Forty-eight PwMS, stratified for ambulation level, will be randomised to control (n=24) or intervention (n=24). Both groups will receive a brochure about fall risk factors and fall prevention. The intervention is group-based (eight PwMS in each group); will be delivered online; and involve six, 2-hour weekly sessions and a booster session 8 weeks after the sixth session. Each intervention group will be led by a trained facilitator. Data collection will be performed at baseline, and after seven and 18 weeks. Outcome measures will capture data on fall prevention behaviours, fear of falling, falls self-efficacy, social and everyday activities, perceived impact of MS and number of falls. Feasibility of recruitment process, data collection procedures, outcome measures, and delivery, and intervention acceptability, fidelity and outcomes will be evaluated. Both quantitative and qualitative methods will be used.Ethics and dissemination Ethical approval has been obtained from the Swedish Ethical Review Authority (registration number 2021-04817). Results will be disseminated in peer-review journals, at conferences, research meetings, in social media and through the patient organisation Neuro Sweden.Trial registration number NCT04317716.